MELATIH KETERAMPILAN MERANGKAI BUNGA AKRILIK MELALUI METODE BERVARIASI BAGI ANAK TUNAGRAHITA RINGAN - Citra Oktavini, Irdamurni, Zumiyetri (Universitas Negeri Padang, 2013)
Coaching Skills Through Acrylic Flower Arrangement Varied Methods for Children mental retardation Lightweight Class SLB Al Hidayah D.VIC in Padang. (Single Subject Research) Thesis. Education, Faculty of Education, State University of Padang. The research was motivated by a child class Lightweight mental retardation D.VIC in SLB Al Hidayah Padang not have acrylic flower arranging skills. There searchers wanted to practice the skills of flower arranging acrylic ATG X through varied methods by way of explaining, demonstrating and directly to the child repeatedly. The length of treatment conditions ten times for ten days. Tendency toward baseline data demonstrated the ability of acrylic flower arranging a little kid up (+), whereasin thetreatment condition showed the acrylic flower child's ability to increase again (+). In the baseline condition of the child's ability level changes acrylic flower arrangement is (+15) capability, for the treatment of rate of changeis (+65) capabilities. Analysis results between conditions showed: The number of variables that changed is that acrylic flower arranging skills, the overlap percentage is 0% means that there is an increasein the ability of ATG X acrylic flower arranging through varied methods in SLB Al Hidayah Padang.